Effectiveness Interest Rate Policy and Inflation in Push Foreign Investment In Indonesia, India, and Vietnam - Safitri, Syifa Arrista Safitr (Journal of Islamic Economic and Business Studies, 2025)
Economic growth is significantly driven by foreign direct investment (FDI), especially in developing countries such as Vietnam, India, and Indonesia. Using annual data from 2017 to 2023, this study uses comparative descriptive techniques and quantitative analysis to assess how well interest rate and inflation policies attract foreign direct investment. Reliable sources, including the World Bank, IMF, and financial institutions in the countries concerned, provide the data. Based on the analysis results, FDI (Y) is significantly negatively affected by the interest rate variable (X1) and positively by inflation (X2). Simultaneous tests show that FDI flows are strongly affected by inflation and interest rates. Based on the study's findings, macroeconomic stability can be achieved through effective control of interests, through proper management of interest rates and inflation, which is the key to increasing the attractiveness of FDI in the three countries. Keywords : interest rates, inflation, FDI, economic stability.